The use of guessing strategies in comprehending idioms by ESL learners / Nur Riza Alias - Nur Riza , Alias (2017)
Second language learners often struggle to understand the messages conveyed when idioms are used in texts or conversations. Due to a huge number of English idioms, it is a challenge for them to understand all the meanings conveyed by these idioms. As a result of this obstacle, learners have to strategize their thoughts by using various guessing techniques to process the information in order to make the meaning of the phrases which sometimes have to be interpreted figuratively. The purpose of the study is to investigate the use of guessing strategies in comprehending idioms among 58 ESL (English as a Second Language) learners in SMK Tanjung Datuk, Johor. Their competency in comprehending idioms will be measured before looking at the guessing strategies used by them to assist their understanding. Two groups of proficiency; proficient and less proficient were the focus for this study to see if there were any differences in terms of their performance in understanding idioms and how they used guessing strategies during the process. The theoretical framework used for the study was the Global Elaboration Model (GEM) proposed by Levorato & Cacciari (1992) to explain the process of comprehending idioms. Forty multiple choice questions in a questionnaire cum test and interviews were used to gather data from the 58 respondents. The findings showed that 45 out of the 58 respondents had an average competency with an appropriate and comprehensive knowledge of idioms with a score between 50 to 79 percent. Only 5 of the respondents were able to demonstrate an exceptional understanding of comprehending the idioms with a score of above 80 percent. Another 7 respondents showed a basic knowledge of idioms with a score of between 40 to 49 percent. Only 1 respondent from this study showed an inadequate knowledge of idioms. “Guessing from context” was used mostly by the proficient respondents in comprehending idioms. 56% of the proficient respondents used “Guessing from context” (GC) when interpreting idioms in context followed by using their background knowledge (BK) as another guessing strategy which was used by 21% of them. Among the less proficient respondents, their highest guessing strategy was also “Guessing from context”’; however, with a smaller number in percentage that is only 36% compared to the proficient respondents followed by 32% using the wild guessing (WG) strategy where they merely chose the meaning of idioms without properly analyzing them. The proficient and less proficient respondents tended to employ guessing from context (GC) as their most preferable guessing strategy, but the main hindrance that stood between them was their lexical knowledge of English. In addition, the proficient and less proficient respondents shared the same lowest guessing strategy which was “referring to L1” strategy which had a 6% frequency usage. This was because the idioms used in the questionnaire were unlikely to have similarity with the respondents’ first language idioms and thus this guessing strategy was the least used strategy compared to the others.